The solution to the above second-order differential equation can be determined as .
It is known that the function evaluated at can be written as
Determine the value of
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For the second-order differential equation we use the auxiliary equation m 2 + m = 0 and we will solve for m . The two roots of the equation will be the exponents of the solution y = C 1 e m 1 + C 2 e m 2 .
From here, we can solve the quadratic auxiliary equation finding the two solutions
m 1 , m 2 = 2 × 1 − 1 ± 1 2 − 4 × 1 × 0 ⇒ m 1 = 0 , and m 2 = − 1
So now we have the solution y = C 1 + C 2 e − x and now we need to plug in those boundary conditions. Well first, we can find that y ′ = − C 2 e − x and we can solve for C 2 . Plugging in our second initial condition y ′ ( ln 2 ) = 1 we see that C 2 = − 2 .
Now we can plug in our first initial condition, much like we did the second and we find that C 1 = C 2 = − 2 . We finally have our solution to the ODE.
f ( x ) = − 2 ( e − x + 1 )
Now let's plug in ln 4
f ( ln 4 ) = − 2 5 and therefore a + b = 5 + 2 = 7